Would perceived organizational spiritual climate matters if spirituality characteristics influenced physicians’ intention to quit? - Vem, Linus Jonathan; Ng, Siew Imm; Sambasivan, Murali; Tee, Keng-Kok (Fundacao Escola de Comercio Alvares (FECAP), 2024)
Purpose – There has been a growing concern about physician turnover in sub-Saharan Africa. In this study, we explore the role of spirituality characteristics (SCs) and perceived organizational spiritual climate (POSC) on turnover intention (TI) among physicians in Nigeria, through the work-home interface (WHI).